Impact of convection on thermographic analysis of silver based thermal joints. Issue 4 (5th June 2020) - Stojek, Krzysztof Jakub; Felba, Jan; Nicolics, Johann; Wołczyński, Dominik
Abstract : Purpose: This paper aims to develop thermal analysis method of thermal joints characterization. The impact on convection on thermal resistance analysis with use thermography for silver-based thermal joints were investigated for non-metallized and metalized semiconductor surfaces. Heat transfer efficiency depends on thermal conductivity; radiation was used to perform thermographic analysis; the convection is energy loss, so its removing might improve measurements accuracy. Design/methodology/approach: Investigation of thermal joints analysis method was focused on determination of convection impact on thermal resistance thermographic analysis method. Measuring samples placed in vacuum chamber with lowered pressure requires transparent window for infrared radiation that is used for thermographic analysis. Impact of infrared window and convection on temperature measurements and thermal resistance were referred. Findings: The results showed that the silicon window allowed to perform thermal analysis through, and the convection was heat transfer mode which create 15% energy loss. Originality/value: It is possible to measure thermal resistance for silver-based thermal joints with convection eliminated to improve measurements accuracy.